Renal Angiomyolipoma During Pregnancy: What Can We Offer? - Lim, PS; Ng, BK; Rozman Z; Nirmala K; Shuhaila A; Omar MH (Faculty of Medicine, UKM Medical Centre, 2015)
Renal angiomyolipoma is a rare disease seen during pregnancy. Rupture of renal angiomyolipoma could be catastrophic and might result in maternal and even perinatal mortality. Management includes conservative vs surgical approach. A 29-year-old woman Para 2 with history of bleeding renal angiomyolipoma in her first pregnancy at 11 weeks treated with selective arterial embolisation. The pregnancy was terminated. Even though having small residual tumour, her subsequent pregnancy progressed well with conservative management. Intervention is advisable in the presence of large or symptomatic renal angiomyolipoma prior to pregnancy in order to minimise potential life-threatening haemorrhage during pregnancy. For those with small tumour of less than 4cm, perhaps conservative approaches i.e. frequent follow-up and close monitoring would assist in early identification of any rupture or bleeding.